Temporal distancing and integrating : Exploring coopetition tensions through managerial sensemaking dynamics - Lundgren-Henriksson, Eva-Lena; Tidström, Annika (Elsevier, 2021)
Despite the growing interest in coopetition management strategies, we still lack detailed insights into how the simultaneity of cooperation and competition is cognitively experienced and coped with at the individual level. Based on two case studies, we introduce sensemaking dynamics deeper into the cognitive management approaches of coopetition tensions by demonstrating temporal distancing and integrating as cognitive activities. Temporal distancing captures the perceived difficulties to connect recalled competitive pasts and imagined cooperative futures, whereas referencing re-imagined pasts and futures enables a connection, i.e. temporal integration, informing managerial actions and coopetition decision-making. First, our study extends theoretical insights on how tensions manifest through managerial sensemaking. Second, we contribute to research on individual level coping strategies part of the coopetition capability concept by showing that managerial mindsets encompass continuous re-imaginations of cooperative and competitive pasts, presents and futures. Third, the findings of our study suggest that managers cope with experienced tensions through their capability to not only re-imagine distant competitive and cooperative pasts and futures, but also through enacting these in the present.
Keywords: Coopetition; tensions; cognition; coping; sensemaking; fi=Strateginen johtaminen|en=Strategic Management|